Digital terrestrial photogrammetry for a dense monitoring of the surficial displacements of a landslide. Issue 1 (August 2021) - Brezzi, L; Vallisari, D; Carraro, E; Teza, G; Pol, A; Liang, Z; Zhou, K; Gabrieli, F; Cola, S; Galgaro, A
Abstract: A new method for measuring spatially dense surface displacements of a landslide at daily intervals and over a long period of time is here presented. The method allows the evaluation of displacements based on a digital image correlation technique applied to a temporal sequence of photos, daily captured by one or more fixed cameras. In comparison to other topographical method this new procedure has a lower accuracy, but provides distributed daily measurements, spatially very dense over the entire landslide area. The multi-view configuration also allows the reconstruction and the update of the 3D surface of the landslide. This work presents some preliminary results obtained by applying this innovative technique to a complex landslide located in the municipality of Perarolo di Cadore (NE Italy), also known as Sant'Andrea landslide. The landslide is characterized by active slow movements involving detrital deposits, about 30 m thick, overlying gypsum-anhydrite rocks. Its activity is strongly correlated to both heavy and long-lasting rain events and to its particular geological conditions. Recently, the alternating phases characterized by slow movements and significant accelerations led to a progressive enlargement of the affected area. Three cameras installed on a stable slope facing the landslide allow to record the intermittent activity and the peculiar behaviour of different parts of the slope. The displacements thus obtained are also compared with those deriving from conventional techniques. Finally, the accuracy of this new method is discussed.